“IMAGE OF VOTERS” IN THE PRE-ELECTION CAMPAIGNS OF PRESIDENTIAL CANDIDATES IN GEORGIA: SOCIETY, PEOPLE, NATION - Maia Bolkvadze,; Ruslan Baramidze, (International Journal of Innovative Technologies in Social Science, 2022)
The paper aims at representing the peculiarities of construction the voters’ image in the pre-election campaigns of the three presidential candidates – Z. Gamsakhurdia, E. Shevardnadze and M. Saakashvili. The voters in their speeches were represented as society, people, citizens, as well as Georgian people or nation. In order to succeed in elections, politicians try (and have) to persuade the electorate in the relevance of their mapped policies, problems and that they offer the best ever solution – for the citizens, people and nation. In order to achieve the set aim, the presidential candidates in Georgia referred to logical reasons, also to well-known symbols, emotive images, various rhetoric strategies - which corresponded to the discourse of respective periods, where the main focus was made on national liberation movement, civil unity, implementing of reforms and etc. Thus, the target of the pre-election texts of the candidates was people (citizens, nation) and the outcomes of the elections were the expression of people’s (citizens, nation) will and desire. Accordingly, the “voters’ image” was constructed under the influence of actual challenges and desires. The deliverables of the researched empiric resources allow us to conclude that the emphasis on justification of the necessity of voters’ participation in the electoral processes is one of the fundamental elements of Georgian political discourse, as the aforesaid device recurrently appeared in all the three presidential candidates’ pre-election speeches. On the other hand, the candidates themselves formulated – who was a voter (as a group, with the respective peculiarities, qualities and needs – best seen by the presidential candidates). Through achieving a unity with the people by means of representing themselves as community leaders, the candidates legitimized their actions justifying them as “authorized by the people”. Therefore, the ballot results expressed the community’s will and desire. The Georgian people and nation were especially visible in Z. Gamsakhurdia’s speeches. He considered Georgian people to be the main decision-making group and focused on other ethnic groups through mutual relationships. E. Shevardnadze’s pre-election texts were devoid of ethnic content. He mentioned Georgian people in relation to culture, state symbols, conflicts, foreign policy only. M. Saakashvili “returned” to talking about Georgian people, yet in his speeches he sometimes referred to the society in Georgia and sometimes expressed ethnic content. Thus, the voter represented “an unchanged group” during the period of its author/creator political leader. A new “image of voters” were created during the next the pre-election campaign by a new political leader. The scientific novelty of the article is the analytical approach to the pre-election political texts (speeches, appeals, statements) of the presidential candidates in Georgia, aiming at researching the construction of Georgian “voter’s image” and reflecting the transformation of particular attitudes and the respective representation of voters in Georgian reality. In practical terms, the paper will be interesting and useful for those scientific circles, students and other people dealing with the issues of political discourse and its formation, as well as for the researchers of public speeches.